Relazione dello scavo del complesso ecclesiale di Nitl. Stratigrafia e ceramica - Hamarneh, B. (Liber Annuus, 2006)
Abstract Continuing from the publication of the Liturgical Complex of Saint Sergius at Nitl (cf. M. Piccirillo - I. Shahid, LA 51 [2001] 267-292) where the importance of the monument for the history of the presence of the Christian confederation of Banu Ghassan in the Arabia Provincia is highlighted, in this article the stratigrafic documentation of the excavation is highlighted, especially that of the southern part of the Church of Saint Sergius and the eastern annexes, together with the related ceramic typology of the different periods of occupation.